Analyzing Interface Recombination in Lead‐Halide Perovskite Solar Cells with Organic and Inorganic Hole‐Transport Layers. Issue 16 (28th June 2020) - Haddad, Jinane; Krogmeier, Benedikt; Klingebiel, Benjamin; Krückemeier, Lisa; Melhem, Stephanie; Liu, Zhifa; Hüpkes, Jürgen; Mathur, Sanjay; Kirchartz, Thomas
Abstract: The interfaces between absorber and transport layers are shown to be critical for perovskite device performance. However, quantitative characterization of interface recombination has so far proven to be highly challenging in working perovskite solar cells. Here, methylammonium lead halide (CH3 NH3 PbI3 ) perovskite solar cells are studied based on a range of different hole‐transport layers, namely, an inorganic hole‐transport layer CuOx, an organic hole‐transport layer poly(triarylamine) (PTAA), and a bilayer of CuOx /PTAA. The cells are completed by a [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PCBM)/bathocuproine/Ag electron contact. Energy levels are characterized using photoelectron spectroscopy and recombination dynamics by combining steady‐state photoluminescence and transient photoluminescence with numerical simulations. While the PTAA‐based devices hardly show any interface recombination losses and open‐circuit voltages >1.2 V, substantial losses are observed for the samples with a direct CuOx /perovskite interface. These losses are assigned to a combination of energetic misalignment at the CuOx /perovskite interface coupled with increased interface recombination velocities at the perovskite/PCBM interface. Abstract : A methodology is developed and applied to study interfacial recombination losses in lead‐halide perovskite‐based solar cells. The study uses a variation of hole‐transport layers in combination with photoelectron spectroscopy, steady‐state and transient photoluminescence, and device simulations to show how to quantify recombination losses due to nonideal band alignment and variations in recombination dynamics.